Farinha de resíduos de filetagem da tilápia para suínos - Richart, Edson (2013)
In order to conduct a nutritional evaluation of meal from tilapia filleting industrial waste (FRIFT) for barrows from 15 to 30 kg, three experiments were accomplished: energy digestibility, amino acids digestibility and animal performance. In the first experiment, the chemical composition and digestible and metabolizable energy of FRIFT was determined, using eight crossbred barrows with average initial weight of 15.10kg ±0.74kg were used, which were distributed individually in metabolism cages. The experimental design was completely randomized with two treatments and four replicates per treatment. The FRIFT replaced 20% the reference diet, based on corn, soybean meal, vitamins, minerals and amino acids. The experimental period lasted 12 days, of which seven to adapt to the cages and the experimental diets and five days for collection of urine and feces. The values of fat, Ca and P of FRIFT, corresponding to 16.82, 6.98 and 3.52%, were higher than those found in the literature. The values of digestible and metabolizable energy of FRIFT corresponded to 3,632 and 3,260 kcal/kg, respectively, for crossbred barrows from 15 to 30 kg. In the second experiment, the coefficients of ileal digestibility of amino acids of FRIFT were determined, having been used 8 crossbred barrows, with an average initial weight of 15.00 ± 0.27 kg, in a completely randomized design with two treatments and four replications and the treatments consisted of a basal diet whose the only protein source was FRIFT, and other protein-free diet, in order to determine the excretion of endogenous amino acids. The basal diet was formulated with sugar, starch, rice hulls, soybean oil, vitamins, minerals and additives. The chromic oxide was used as an indicator in determining the digestibility coefficients. The animals were fed twice daily, based on metabolic size, during 6 days. The pigs were then submitted to the collection of ileal digesta, by the method of sacrifice. The dry matter, crude protein, amino acid and chromic oxide of digesta, rations and feeds were determined. The endogenous loss of amino acids was variable, as leucine and threonine showed the greatest losses, of 33 and 28 mg / kg DIP consumed, respectively. The coefficients of true ileal digestibility of amino acids of FRIFT for arginine, lysine and methionine were 84.46, 76.60 and 82.43%, respectively, similar to those proposed in contemporary literature. In the third experiment, the growth performance and economic were evaluated for barrows fed diets containing different levels of FRIFT. A total of 40 crossbred barrows with an initial weight of 15.00 ± 0.87 kg were used in a randomized block design, with five treatments (0, 5, 10, 15 and 20% FRIFT), 4 replicates and 2 animals per experimental unit, distributed in treatments based on kinship and initial weight. The animals were housed in demonstrative experimental nursery endowed with elevated metal pens, polypropylene floor and screened sides, equipped with semi-automatic feeders and nipple drinkers, located in masonry building. The experimental diets were formulated based on corn, soybean meal, minerals, vitamins, amino acids and additives. Levels of 0 to 10% of FRIFT inclusion in the diets did not affect the final weight (FW) and average daily gain (ADG) of pigs by Dunnett test (P<0.05), but 15% of FRIFT inclusion resulted in decrease of FW and ADG. The average values of feed conversion (FC) were different (P<0.05) by Dunnett test only for the highest level of FRIFT inclusion in relation to the reference diet. For this level (20% FRIFT), there was increase in FC and therefore worsening in pigs performance. There was decreasing linear effect of levels of FRIFT on variables FW (P=0.01), ADG (P=0.01) and increased linear effect on FC (P=0.01). There was no difference (P>0.05) for the total cost of ration (TCR) in any level of inclusion of FRIFT by Dunnett test, compared with the reference diet. Even though, the proportional gain of pigs (PGP) and bioeconomic index (BI) had the best results (P<0.05) only for the reference diet, and 5% of FRIFT has worsened in results. The ratio proportional gain of pigs: feed cost (PGP:FC) worsened (P<0.05) with 10% of FRIFT inclusion in the diets. Levels up to 10% of FRIFT inclusion in diets for barrows from 15 to 30kg, replacing soybean meal, did not harm the ADG and FC of the animals. However, the inclusion of 5% FRIFT impaired the economic performance, making it impracticable to include this food in diets for starting pigs